The Influence of the Wavelength of Laser Light on the Non-Contact Measurement of the Roughness of Shiny Cut Surfaces on Stainless Steel A304 Material - Juraj Ružbarský (Applied Sciences, 2024)
The article is focused on the study of the effect of laser light with three wavelengths used in a laser profilometer for the measurement of selected roughness parameters of the shiny surface of stainless steel A304 material. The measured results were compared with the results we achieved with the reference contact roughness meter (SJ-400). The findings presented are relevant to the parameters of the experiment outlined within the article. In general, the obtained results make it possible to state that when measuring the roughness of shiny cut surfaces using non-contact laser profilometry, reflections of laser light occur. The relatively best results of measuring the parameters of the roughness of a shiny cut surface on the evaluated material (A304) were achieved by laser light with a wavelength of λ = 445 nm. In contrast, as the surface roughness of the cutting surface of the used material increased, the reflection of laser light decreased. Furthermore, we can state that the values of the roughness parameters Ra and Rz of the shiny surface measured by laser profilometry were several times higher than the values measured by the reference method. In contrast, the non-contact method of laser profilometry is not suitable for accurate measurements of the roughness parameters of shiny surfaces.